Instytucje otoczenia biznesu jako czynnik wspomagający rozwój przedsiębiorczości w woj. podkarpackim - Cebulak, Jan (Przedsiębiorczość - Edukacja, 2009)
Institutional infrastructure, consists of economic development agencies, commerce and industrychambers, banks, loan and saving funds, investment companies, development funds, economicsupport funds, insurance companies etc., is the signiﬁcant factor in regional development. ThePodkarpacie region has a great institutional potential for the support in the regional development;potential equal to the Małopolskie region with highest level of economic development. Thispotential is not fully used for the directions of the regional development deﬁned in theaccepted strategies and in other agendas for Podkarpacie.